2021
DOI: 10.1021/acsbiomaterials.1c00514
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Coated MCM-41 Mesoporous Silica Nanoparticles Loaded with Berberine Improved Inhibition of Acetylcholine Esterase and Amyloid Formation

Abstract: Selective permeability of the blood–brain barrier limits effective treatment of neurodegenerative disorders. In the present study, brain-targeted lipid-coated mesoporous silica nanoparticles (MSNs) containing berberine (BBR) were synthesized for the effective treatment of Alzheimer’s disease (AD). The study involved synthesis of Mobil Composition of Matter-41 (MCM-41) mesoporous silica nanoparticles (MSNs), BBR loading, and lipid coating of MSNs (MSNs-BBR-L) and in vitro and in vivo characterization of MSNs-BB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 86 publications
1
49
0
Order By: Relevance
“…Taken together, our findings indicate that fine-tuning the geometry of nanoparticles may influence their biological fate, such as increased cellular uptake and oral bioavailability [23]. Lipid-coated nanoparticles are found to be effective in overcoming epithelial barriers [40]. The particle absorption takes place due to their strong interaction with cell lipid bilayers.…”
Section: Msn As a Drug Carrier: Mechanisms To Overcome Oral Barriersmentioning
confidence: 68%
See 2 more Smart Citations
“…Taken together, our findings indicate that fine-tuning the geometry of nanoparticles may influence their biological fate, such as increased cellular uptake and oral bioavailability [23]. Lipid-coated nanoparticles are found to be effective in overcoming epithelial barriers [40]. The particle absorption takes place due to their strong interaction with cell lipid bilayers.…”
Section: Msn As a Drug Carrier: Mechanisms To Overcome Oral Barriersmentioning
confidence: 68%
“…It is mainly used to protect the drug from various hydrolytic enzymes, improve residence time, increase the absorption as well as the bioavailability. Various nanocarriers for oral drug delivery include polymeric nanocarriers, inorganic nanocarriers, solid lipids as nanocarriers, mesoporous silica nanoparticles, and metallic nanoparticles [4,17,30,32,34,37,40,52,62,64,83]. Silica based nano carriers for delivery of drugs, biomolecules, and food are an emerging highlight.…”
Section: Comparison Of Oral Carriers and Delivery Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological state of the brain is quite different to that of other organs because the BBB is a primary obstacle for drug delivery to the brain [25,26]. For this reason, various delivery platforms have been investigated to improve the penetration and/or transport of bioactive agents [26][27][28][29][30][31][32][33][34][35][36][41][42][43][44][45][46][47]. For example, surfactants such as polysorbate 80 have been used to allow nanoparticles or drug carriers to penetrate the BBB [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that nanocomposites significantly increased the level of adenosine phosphate, reduced the oxidative stress and reversed dopaminergic neuronal damage. Berberine-encapsulated mesoporous silica nanoparticles effectively inhibited amyloid fibrillation and decreased the level of malondialdehyde [36]. Lee et al reported that redox-responsive nanoparticles have sensitivity to ROS formation in cancer cells and that the release rate of anticancer drugs can be controlled by intracellular oxidative stress in cancer cells [37].…”
Section: Introductionmentioning
confidence: 99%